Career Guidance in the Context of Improving the Labor Market - Liudmila NADREEVA; Vladimir ABRAMOV; Anna NIKOLAEVA (Communications of International Proceedings, 2021)
In modern Russian society, the policy pursued by the state is far from perfect, which leads to a high occurrence of errors in the choice of profession and does not contribute to the effective formation of the labor market workforce.
Keywords: Profession; career guidance; self-determination; event marketing; event marketing; field of activity; career guidance project; survey; employment; labor market.